2021
DOI: 10.1111/ijcp.14692
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic damage in COVID‐19: Why? How?

Abstract: Object We aimed to evaluate the elevation of amylase and lipase enzymes in coronavirus disease 2019 (COVID‐19) patients and their relationship with the severity of COVID‐19. Method In this study, 1378 patients with COVID‐19 infection were included. Relation of elevated amylase and lipase levels and comorbidities with the severity of COVID‐19 was analysed. The effects of haemodynamic parameters and organ failure on pancreatic enzymes and their relations with prognosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
3
19
2
3
Order By: Relevance
“…Since the heterogeneity was significant, we performed a sensitivity analysis to explore the impact of each study. The result showed that two studies ( 13 , 23 ) affected the pooled OR (odds ratio) of mortality ( Supplementary Figure 2 ). After removing any one of the two studies, the I 2 did not decrease significantly (78.6–87.7%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the heterogeneity was significant, we performed a sensitivity analysis to explore the impact of each study. The result showed that two studies ( 13 , 23 ) affected the pooled OR (odds ratio) of mortality ( Supplementary Figure 2 ). After removing any one of the two studies, the I 2 did not decrease significantly (78.6–87.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies ( 13 , 14 , 21 , 22 , 25 , 26 ) with samples more than ten patients reported AP diagnosis according to the revised Atlanta classification of acute pancreatitis 2012 ( 30 ), covering 1,705 patients with elevated PE > 3 × ULN, of which 182 developed AP. The prevalence of AP ranged from 1.3 to 18.8%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, in this study, GGT values in the group with high lipase activity were significantly higher than in the group with normal lipase activity; however, GGT was not one of the independent factors that was determined to predict mortality successfully in this patient population. In a study including 1378 COVID-19 patients, it was reported that high amylase activity was associated with severe disease outcomes [ 31 ]. In comparison, in this study, a weak correlation was found between high amylase activity measured at admission and mortality.…”
Section: Discussionmentioning
confidence: 99%